Splicing Factor Mutations in Myelodysplasias: Insights from Spliceosome Structures - Jenkins, Jermaine L. (Trends Genet, 2017)
Somatic mutations of pre-mRNA splicing factors recur among patients with myelodysplastic syndromes (MDS) and related malignancies. Although these MDS-relevant mutations alter splicing of a subset of transcripts, the mechanisms by which these single amino acid substitutions change gene expression remain controversial. New structures of spliceosome intermediates and associated protein complexes shed light on the molecular interactions mediated by “hotspots” of the SF3B1 and U2AF1 pre-mRNA splicing factors. The frequently mutated SF3B1 residues contact the pre-mRNA splice site. Based on structural-homology with other spliceosome subunits and recent findings of altered RNA binding by mutant U2AF1 proteins, we suggest that affected U2AF1 residues also contact pre-mRNA. Altered pre-mRNA recognition emerges as a molecular theme among MDS-relevant mutations of pre-mRNA splicing factors.